Penerapan Asesmen Perkembangan dan Akademik pada Anak Berkebutuhan Khusus Kategori Slow Learner dan Fast Learner (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study identifies the implementation of developmental and academic assessments for children with special needs categorized as slow learners and fast learners within inclusive education. Using a qualitative descriptive approach conducted on December 9, 2025, data were collected through observation, interviews, and documentation at the homes of two children. The data were analyzed using the Miles and Huberman model and triangulation techniques. The results of the academic assessment reveal significant differences: slow learners show limitations in basic reading, writing, and numeracy skills, requiring a gradual and structured approach, while fast learners demonstrate superior abilities in complex comprehension and initiative. Developmental assessments indicate that slow learners experience delays in cognitive, socio-emotional, language, and fine motor aspects, whereas fast learners perform optimally across all developmental domains. Assessment serves as the foundation for individualized strategies: concrete and repetitive instruction for slow learners, and enrichment and project-based activities for fast learners, supporting equitable inclusion and the maximization of each child’s potential.